Association between bone mineral density and stroke: a meta-analysis - Zhao, Peng; Sun, Huaxia (Frontiers in Neurology, 2025)
ObjectiveThe correlation between bone mineral density (BMD) and stroke remains inconsistent. This study aims to determine whether a reduction in BMD is associated with an increased risk of stroke.MethodsWe systematically searched Medline, Embase, and the Cochrane Database of Systematic Reviews through January 2025 to identify cohort studies with follow-up that reported the influence of a reduction in BMD or low BMD status on the risk of any type of stroke. Pooled analyses were performed using random-effects models.ResultsThis study included 13 studies with 146,758 individuals. A 1 SD reduction in BMD was associated with an increased risk of stroke (eight studies; RR, 1.24; 95% CI, 1.09–1.40; p < 0.001; I2 = 87%). Subgroup analysis showed that a per SD reduction in BMD was associated with incident stroke in female persons (eight studies; RR, 1.28; 95% CI, 1.09–1.51; p = 0.002; I2 = 87%), but not in male persons (four studies; RR, 1.04; 95% CI, 0.99–1.10; p = 0.15; I2 = 0%). People with osteoporosis or osteopenia had an increased risk of incident stroke (six studies; RR, 1.59; 95% CI, 1.22–2.08; p < 0.001; I2 = 92%), as well as male persons (two studies; RR, 3.16; 95% CI, 1.96–5.12; p < 0.001; I2 = 35%). Sensitivity analysis showed that the results were stable.ConclusionReduction in BMD is associated with a significantly increased risk of stroke. Female individuals have a higher risk than male persons.